Directions of effects between self-criticism and parental support on adaptive goal pursuit among emerging adults. (October 2016) - Dickson, Daniel J.; Shulman, Shmuel
Abstract: While most parents continue to support their children into adulthood, it is not known if parents of distressed young adults withdraw support like they tend to do with difficult children. The present study examines the direction of effects between offspring perceived parental support, young adult self-criticism, and goal outcomes (attainment & importance) at three time points across ages 23 to 26 in a sample of 205 Israeli emerging adults (118 men and 87 women). Results indicated that higher levels of parental support directly predicted increases in offspring's goal attainment. In addition, higher levels of parental support indirectly predicted increases in goal attainment and goal importance via reductions in self-criticism. However, self-criticism did not affect parental support over time. Findings of this study extend upon previous cross-sectional findings while further demonstrating that parents continue acting as a valuable source of direction and guidance, thereby limiting offspring's goal-oriented distress, and fostering security and self-confidence during the important transitional period to adulthood. Highlights: Parental support of young adults facilitate over time increases in goal attainment. Parental support decreases young adults' goal-oriented self-criticism and distress. Parents' contributions to reductions in self-criticism indirectly promote adaptation.